Congenital mesenteric hernia in neonates: Still a dilemma - Parkash Mandhan; Noora Alshahwani; Zainab Al-Balushi; Anwar Arain (Wolters Kluwer Medknow Publications, 2015)
Congenital transmesenteric hernia in neonates is a rare cause of intestinal obstruction with devastating outcomes and still remains a challenge to diagnose pre-operatively. Patients are often managed with emergency surgical exploration and may need bowel resection. We present 2 neonates with small bowel obstruction secondary to strangulated transmesenteric hernia through a congenital defect in the small bowel mesentery, which were managed successfully. We have also reviewed the literature about congenital transmesenteric hernia in neonates.